Determination of genetic diversity and inbreeding level in deli dura and AVROS advanced breeding materials in oil palm (Elaeis guineensis jacq.) using microsatellite markers - Tay, Chee Chun (2016)
Intensive selections in breeding have led to a narrowed genetic diversity in oil palm. Although uniformity is favorable to breeders, loss of genetic diversity may lead to deleterious consequences. Thus, background knowledge on genetic diversity in advanced breeding material of oil palm (Elaeis guineensis Jacq.) is critical for crop improvement. The objectives of the study are to evaluate the genetic diversity in the advanced breeding materials, Deli dura and AVROS populations, and to determine the levels of inbreeding in these populations using CIRAD’s Simple Sequence Repeat (SSR) markers. The parental populations evaluated here were 186 palms from 8 DxD/D-selfs Deli dura and 188 palms from 8 TxT/T-selfs AVROS progenies sourced from Agency 1 and Agency 2. Ekona population was included as control. Genotyping was done by using 32 SSR markers which produced 230 alleles among the 17 oil palm progenies. The number of alleles scored per SSR primer ranged between 4 to 11. The average number of alleles per locus was 7.1875. The expected heterozygosity (He) and observed heterozygosity (Ho) among the populations were 0.7063 and 0.5270, respectively. Genetic distance values were calculated. The dendogram resulting from the Neighbour-Joining clustering analysis revealed that the 17 populations were clustered into 3 main clusters namely Deli dura, AVROS and Ekona populations. The AVROS cluster was further divided into two sub-clusters according to Agency. The Deli dura cluster was sub-clustered based on the cross type i.e. DxD and D-selfs. The two different generations of AVROS provided an overview of the inbreeding level in the AVROS population. AVROS from Agency 2 had inbreeding coefficient of 0.0336 compared to AVROS from Agency 1 which was -0.0810. The inbreeding value indicated that Agency 2 AVROS had lower heterozygosity compared to Agency 1. The genetic variability revealed via SSR markers on the advanced breeding populations provide a better understanding to the breeder and the information can guide them in decision making during the inbred lines development.